The Use of Folklore E-Books in Introducing Archaic Vocabulary for Elementary School Students - Kusumajanti, Wahju (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This study aims to determine the number and meaning of archaic vocabulary in the literacy discourse of the e-book